2008
DOI: 10.1016/j.cca.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Fractions of plasma gamma-glutamyltransferase in healthy individuals: Reference values

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 10 publications
1
51
0
2
Order By: Relevance
“…enzyme ␥-glutamyltranspeptidase (11), which may contribute to accelerating isotopic equilibration as well as degradation of GSH.…”
mentioning
confidence: 99%
“…enzyme ␥-glutamyltranspeptidase (11), which may contribute to accelerating isotopic equilibration as well as degradation of GSH.…”
mentioning
confidence: 99%
“…However, Huo et al (2011) studied the antioxidant and hepatoprotective effect of licorice aqueous extract against the oxidative damage induced by CCl 4 (3 mL kg -1 ) in rats and the results showed that all tested concentrations (100, 150 and 300 mg kg -1 ) effectively protected the liver of animals, and the protective effect of the extract was evidenced by a decrease in the levels of AST and ALT. Frazini et al (2008) and Teixeira et al (2009) reported that ALT is found primarily in the liver, and considered a more sensitive indicator than AST, since it exists in all body tissues, especially the heart, liver, skeletal muscle, kidneys, brain, pancreas, leukocytes, erythrocytes. GGT is a glycoprotein enzyme regularly attached to the cell membrane and participates in the transport of amino acids and peptides to cells and tissue glutathione levels.…”
Section: Resultsmentioning
confidence: 99%
“…Сывороточный фермент имеет множественные формы, выявленные с помощью высокоэффективной жидкостной хроматографии и, вероятно, связанные с посттрансляционной модификацией, которую определяют множественные сайты гликозилирова ния на поверхности белка [14].…”
Section: структура и основные свойства ггтпunclassified
“…3. Схема посттрансляционной модификации белков путем S глутатио нирования и S нитрозилирования [38] 10 атеросклероза, метаболического синдрома, сахар ного диабета 2 го типа, сердечно сосудистых забо леваний выявляются, когда значения активности фермента находятся в пределах верхнего квартиля референсных значений [14,22,26,27]. Из этого сле дует, что референсные интервалы должны быть определены с учетом возрастных, гендерных, нут риентных и других факторов в популяции.…”
Section: связь ггпт с патологическими процессамиunclassified